2020
DOI: 10.1017/s0007114520003736
|View full text |Cite
|
Sign up to set email alerts
|

Casein glycomacropeptide is well tolerated in healthy adults and changes neither high-sensitive C-reactive protein, gut microbiota nor faecal butyrate: a restricted randomised trial

Abstract: Casein glycomacropeptide (CGMP) is a bioactive milk-derived peptide with potential anti-inflammatory effects. Animal studies suggest that CGMP may work by altering gut microbiota composition and enhancing butyrate production. Its effects on intestinal homeostasis, microbiota and metabolites in humans are unknown. The aim of the present study was to assess both the intestinal and systemic immunomodulatory effects of orally ingested CGMP. We hypothesised that a daily oral CGMP intake would reduce high-sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…On the other hand, in humans, a 4-week randomized study conducted on twenty-four healthy subjects in 2021 has found no differences in fecal microbiota composition between adults consuming GMP or placebo. Similarly, no differences were found in body weight, fecal calprotectin, and SCFA levels at baseline and at week 4 between the two groups [29].…”
Section: Discussionmentioning
confidence: 76%
“…On the other hand, in humans, a 4-week randomized study conducted on twenty-four healthy subjects in 2021 has found no differences in fecal microbiota composition between adults consuming GMP or placebo. Similarly, no differences were found in body weight, fecal calprotectin, and SCFA levels at baseline and at week 4 between the two groups [29].…”
Section: Discussionmentioning
confidence: 76%
“…Though GMP has growth-promoting effects on probiotic organisms in vitro and in animal models, these results are not consistently replicable in humans. Wernlund et al (2020) found that GMP supplementation in healthy human subjects had no effects on Shannon or observed diversity and no changes in microbiome composition or fecal SCFAs. Moreover, that study showed no effect of GMP on gastrointestinal symptoms.…”
Section: Effects Of Glycomacropeptide On the Microbiome In Humansmentioning
confidence: 88%
“…Using animal models, GMP is reported as non-immunogenic [39]. It is also safe and well-tolerated by humans, with no immunomodulatory effects in healthy adults [40]. Nevertheless, there are no studies about the possible effects of GMP on keratinocytes, either orally or topically administered.…”
Section: Discussionmentioning
confidence: 99%